Ansiedad hacia las matemáticas de estudiantes de quinto y noveno grado del liceo femenino Mercedes Nariño y las actitudes que perciben de sus maestros. (2020)
This research work aimed to determine what is the level of anxiety that fifth and ninth grade students of the Liceo Femenino Mercedes Nariño have towards mathematics and their attitudes they perceive from their math teacher, and whether there are differences between the grades. For this reason, the Fennema and Sherman instrument (1976) was used, which is made up of nine subscales which can be used individually or together, two of these subscales were used. 295 students participated, 43% of fifth-grade students, the results indicate that if there is a significant and positive correlation between the two variables, in addition to each of the grades, it was also identified that there are no significant relationships between one grade and another.